THE INFLUENCE OF ACADEMIC SUPERVISION AND PRINCIPAL POLICIES ON THE QUALITY OF VOCATIONAL SCHOOL EDUCATION AT KUTAI KARTANEGARA REGENCY - Yudo Dwiyono; Warman Warman; Dicky Kurniawan (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
This study aims (1) to find out the effect of principal academic supervision on the quality of education of Vocational High School at Kutai Kartanegara Regency, (2) to find out the effect of principal policies on the quality of education of Vocational High School at Kutai Kartanegara Regency, (3) to find out the effect of academic supervision and policy, the principal simultaneously on the quality of Vocational High School at Kutai Kartanegara Regency. This research was conducted in Kutai Kartanegara Regency. The method used in the research was correlational method. The data collection technique used a questionnaire that had been tested for its' validity and reliability. Total population of 113 people with a sample of 88 people who were taken by disproportionate stratified random sampling. The data analysis technique used descriptive statistics. The results showed that: (1) Academic supervision has an effect on the quality of education. This means that the higher academic supervision is, it will result in an increasing quality of education, (2) Principal's policy affects the quality of education. This means that the higher the principal's policy is, will result in an increase in the quality of education, (3) Academic supervision and the principal's policy simultaneously affect the quality of education. will result in an increasing quality of education.